A preparation method of micro-nano inorganic particle PP composite material

By using the three-dimensional network structure formed by micro-nano-inorganic particles and spiral fibers in PP materials, the problem of unstable mechanical properties of PP materials is solved, and its tensile strength, bending strength and fracture resistance are significantly improved.

CN118812952BActive Publication Date: 2025-02-11SUZHOU ANMEI MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411074217.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-02-11
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

The mechanical properties of existing PP materials are poor, especially in terms of tensile strength and elastic modulus, and poor impact resistance, which limits the expansion of their application fields.

Method used

The mechanical properties of PP materials are enhanced by the use of micro-nano-inorganic particles. The specific method is to use the micro-crosslinked structure obtained by carbonization of starch and form a three-dimensional structure with network interpenetration by doping spiral fibers to enhance the stability and crack resistance of the material. .

Benefits of technology

It significantly improves the tensile strength, bending strength and fracture resistance of PP materials, reduces the concentration of stress, and enhances the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004981732670000131
    Figure BDA0004981732670000131
Patent Text Reader

Abstract

The present invention provides a method for preparing a micro-nano inorganic particle PP composite material, comprising the following steps: mixing PP granules, micro-nano inorganic particles and a dispersant; adding them into a twin-screw extruder for melt blending, extrusion and granulation to obtain granules; drying the granules, and then injection molding them using an injection molding machine. The present invention uses micro-nano inorganic particles to enhance the mechanical properties of PP materials. The micro-nano inorganic particle matrix is ​​a micro-crosslinked structure obtained by carbonizing starch and formed by interconnecting microgel particles through physical forces. Then, by doping spiral fibers, a network interpenetrating three-dimensional structure is formed, and the stability of the micro-crosslinked structure is further enhanced. When the material is subjected to a load, the stress is first borne by the three-dimensional structure, then propagated to the carbonized spiral fibers, and finally evenly distributed in the microgel particles, thereby reducing stress concentration and improving the material's fracture resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional plastics, and in particular to a method for preparing a micro-nano inorganic particle PP composite material. Background Art

[0002] Polypropylene (PP) materials are widely used in cement roads, auto parts, plastic daily necessities, sports goods, and safety protection due to their low density, good chemical corrosion resistance, high cost performance, and simple processing technology. However, as a thermoplastic fiber, the mechanical properties of PP materials are unstable, and it is easy to have problems such as reduced tensile strength and elastic modulus, and poor impact resistance, which limits the further expansion of the application field of PP fibers. To this end, researchers have carried out a series of modification studies on PP materials. For example, Miao et al. studied the effect of compatibilizers on the interfacial bonding force of graphene oxide / polypropylene composite fibers by regulating the type and amount of compatibilizers in composite materials; Tambe et al. prepared composite materials filled with amine-functionalized multi-walled carbon nanotubes and studied the relationship between their structure and properties; Chi Wenzhong et al. enhanced the mechanical properties of polypropylene composites by changing the size and proportion of the added slag powder, and improved the dispersion uniformity of slag-reinforced polypropylene composite fibers in cement-based mortar. However, in summary, the addition of micron-sized fillers can significantly increase the tensile strength of the composite material, but the bending strength is relatively low. Compared with micron-sized fillers, nano-sized fillers have the advantages of fewer surface defects, high bonding quality with the matrix and strong flowability, but they inevitably lead to agglomeration inside the matrix. Therefore, how to achieve common advantages and achieve comprehensive improvement of mechanical properties is an urgent problem to be solved. Summary of the invention

[0003] Technical problem to be solved: The present invention aims to solve the technical problem of poor mechanical properties of current PP materials by adopting micro-nano inorganic particles to enhance the mechanical properties of PP materials. The micro-nano inorganic particle matrix is ​​a micro-cross-linked structure obtained by carbonizing starch and formed by microgel particles connected to each other by physical force. The network is then interpenetrated by doping spiral fibers to form a three-dimensional structure, which further enhances the stability of the micro-cross-linked structure. When the material is subjected to load, the stress is first borne by the three-dimensional structure, then propagates to the carbonized spiral fibers, and finally evenly distributed in the microgel particles, thereby reducing stress concentration. At the same time, the microgel particles can also hinder the expansion of cracks. When cracks appear in the material, the particles can serve as obstacles to crack expansion, increase the path of crack expansion, and improve the material's resistance to fracture.

[0004] Technical solution: A micro-nano inorganic particle PP composite material, comprising the following components by weight: 100 parts of PP, 8-10 parts of micro-nano inorganic particles and 2 parts of dispersant;

[0005] The particle size of the micro-nano inorganic particles is ≤75 μm.

[0006] Furthermore, the preparation method of the micro-nano inorganic particles is as follows, in parts by weight:

[0007] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0008] Step 2: Add 2-3 parts of sodium trimetaphosphate and 0.8-1 parts of sodium hydroxide, and stir well to mix;

[0009] Step 3: Add 3-6 parts of spiral fibers, continue to stir evenly, and heat in a 40°C water bath for 1-1.5 hours to form a microgel doped with spiral fibers;

[0010] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0011] Step 5: Wash it with water and ethanol in turn, and dry it;

[0012] Step 6: Immerse in silica-alumina sol, stir for 10-20 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0013] Step 7: Place in an argon protected tube furnace, raise the temperature from room temperature to 850-950°C at a heating rate of 1°C / min, and keep at this temperature for 3-4h;

[0014] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles.

[0015] Furthermore, the spiral fiber has a diameter of 0.4-3.6 μm and an aspect ratio of 60-130.

[0016] Furthermore, the preparation method of the spiral fiber is:

[0017] (1) taking discarded coconut shell fiber, adding water to steam after loosening, washing and drying to obtain clean coconut shell fiber;

[0018] (2) adding a NaOH solution with a concentration of 15-20 g / L and a solid-liquid weight ratio of 1:(10-20), pre-soaking at 60-90° C. for 20-60 min, stirring and synchronously ultrasonically oscillating for 2-3 h, and then cyclically extruding and dehydrating and washing with water for 1-3 times to obtain a coconut shell fiber web; (3) extruding and dehydrating the coconut shell fiber web and performing multi-stage drawing treatment to form spiral fibers, which are then dried.

[0019] Furthermore, the silica sol concentration in the silica-alumina sol is 2.5-3.5%, and the aluminum sol concentration is 3.0-3.5%.

[0020] Furthermore, the alumina-silica sol is used to convert Na 2 SiO 3 and Al 2 (SO 4 ) 3 Prepared from aqueous solution.

[0021] Furthermore, the dispersant includes polyethylene wax, sodium lauryl sulfate, oxidized polyethylene wax and vinyl bisstearamide. The preparation method of the above-mentioned micro-nano inorganic particle PP composite material comprises the following steps:

[0022] (1) Mix PP pellets, micro-nano inorganic particles and a dispersant;

[0023] (2) adding the mixture into a twin-screw extruder for melt blending and extrusion granulation to obtain pellets, wherein the temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0024] (3) After the pellets are dried, they are injection molded using an injection molding machine.

[0025] Furthermore, the screw length-to-diameter ratio of the twin-screw extruder is 40:1, and the screw speed is 35 rpm.

[0026] Furthermore, the injection molding conditions are: melt temperature of 200° C., screw speed of 35 rpm, mold temperature of 90° C., and injection pressure of 80 MPa.

[0027] Beneficial effects:

[0028] 1. The present invention enhances the mechanical properties of PP materials by using micro-nano inorganic particles. The micro-nano inorganic particle matrix is ​​a micro-cross-linked structure obtained by carbonizing starch and formed by microgel particles connected to each other by physical force. The network interpenetrating three-dimensional structure is formed by doping spiral fibers, which further enhances the stability of the micro-cross-linked structure. When the material is subjected to a load, the stress is first borne by the three-dimensional structure, then propagated to the carbonized spiral fibers, and finally evenly distributed in the microgel particles, thereby reducing stress concentration. At the same time, the microgel particles can also hinder the expansion of cracks. When cracks appear in the material, the particles can serve as obstacles to crack expansion, increase the path of crack expansion, and improve the material's resistance to fracture.

[0029] 2. In the present invention, since the microgel particles exist in the form of micro-nano inorganic particles, they can be dispersed more evenly in the PP material, which is more helpful to reduce stress concentration and improve the overall performance of the PP material.

[0030] 3. The micro-nano inorganic particles in the present invention can increase the contact area with the PP matrix through their unique surface morphology - the simultaneous existence of particles, fibers and networks (points, lines, surfaces) and physical and chemical properties, forming a stronger interface bonding force, thereby effectively transmitting and dispersing stress.

[0031] 4. The microgel structure and fiber toughness after carbonization in the present invention are relatively poor, and silica-alumina sol is used to toughen the microgel structure. During the gelation process, the silica-alumina sol gradually polymerizes on the fiber surface to form a nanoscale three-dimensional network structure, blocking the fracture lines, while further dispersing the stress and improving the mechanical properties of the material.

[0032] 5. The present invention adopts spiral fibers. Due to its spiral structure, the contact area between the spiral fibers and the micro-cross-linked structure is larger, forming a tighter network structure. The contact area between the spiral fibers and the matrix material is also larger, which can improve the interfacial adhesion and thus improve the overall performance of the composite material. At the same time, the spiral shape is also more conducive to dispersing and absorbing force, hindering the expansion path of cracks and increasing the difficulty of crack expansion, thereby improving the tensile strength and toughness of the PP material. DETAILED DESCRIPTION

[0033] Example 1

[0034] The preparation method of spiral fiber is as follows:

[0035] (1) taking discarded coconut shell fiber, adding water to steam after loosening, washing and drying to obtain clean coconut shell fiber;

[0036] (2) adding a NaOH solution with a concentration of 18 g / L and a solid-liquid weight ratio of 1:15, pre-soaking at 90° C. for 50 min, stirring and synchronously ultrasonically vibrating for 3 h, and then cyclically extruding and dehydrating and washing with water for 3 times to obtain a coconut shell fiber web;

[0037] (3) The coconut shell fiber web is subjected to extrusion dehydration and multi-stage drawing treatment to form spiral fibers, which are then dried.

[0038] The diameter of the helical fibers is 0.4-3.6 μm, and the aspect ratio is 60-130.

[0039] Example 2

[0040] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0041] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0042] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0043] Step 3: Add 3 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0044] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0045] Step 5: Wash it with water and ethanol in turn, and dry it;

[0046] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0047] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0048] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0049] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0050] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0051] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0052] Example 3

[0053] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0054] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0055] Step 2: Add 4 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0056] Step 3: Add 3 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0057] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0058] Step 5: Wash it with water and ethanol in turn, and dry it;

[0059] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0060] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0061] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0062] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0063] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0064] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0065] Example 4

[0066] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0067] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0068] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0069] Step 3: Add 5 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0070] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0071] Step 5: Wash it with water and ethanol in turn, and dry it;

[0072] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0073] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0074] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0075] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0076] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0077] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0078] Example 5

[0079] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0080] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0081] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0082] Step 3: Add 6 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0083] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0084] Step 5: Wash it with water and ethanol in turn, and dry it;

[0085] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0086] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0087] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0088] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0089] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0090] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0091] Example 6

[0092] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0093] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0094] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0095] Step 3: Add 5 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0096] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0097] Step 5: Wash it with water and ethanol in turn, and dry it;

[0098] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 2.5% and the aluminum sol concentration is 3.0%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0099] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0100] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0101] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0102] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0103] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0104] Example 7

[0105] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0106] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0107] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0108] Step 3: Add 5 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0109] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0110] Step 5: Wash it with water and ethanol in turn, and dry it;

[0111] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.5% and the aluminum sol concentration is 3.5%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0112] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0113] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0114] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0115] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0116] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0117] Example 8

[0118] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0119] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0120] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0121] Step 3: Add 5 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.0 h to form a microgel doped with helical fibers;

[0122] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0123] Step 5: Wash it with water and ethanol in turn, and dry it;

[0124] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0125] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0126] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0127] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0128] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0129] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0130] Example 9

[0131] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0132] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0133] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0134] Step 3: Add 5 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0135] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0136] Step 5: Wash it with water and ethanol in turn, and dry it;

[0137] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0138] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0139] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0140] Step 9: Mix 100 parts of PP pellets, 8 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0141] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0142] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0143] Example 10

[0144] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0145] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0146] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0147] Step 3: Add 5 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0148] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0149] Step 5: Wash it with water and ethanol in turn, and dry it;

[0150] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0151] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0152] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0153] Step 9: Mix 100 parts of PP pellets, 10 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0154] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0155] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0156] Embodiment 11

[0157] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0158] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0159] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0160] Step 3: Add 5 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0161] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0162] Step 5: Wash it with water and ethanol in turn, and dry it;

[0163] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0164] Step 7: Place in an argon protected tube furnace, heat from room temperature to 850°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0165] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0166] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0167] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0168] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0169] Example 12

[0170] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0171] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0172] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0173] Step 3: Add 5 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0174] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0175] Step 5: Wash it with water and ethanol in turn, and dry it;

[0176] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0177] Step 7: Place in an argon protected tube furnace, heat from room temperature to 950°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0178] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0179] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0180] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0181] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0182] Comparative Example 1

[0183] The difference between this embodiment and embodiment 4 is that the spiral fibers are changed into straight fibers, specifically:

[0184] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0185] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0186] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0187] Step 3: Add 5 parts of linear fibers with a diameter of 0.4-3.6 μm, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with linear fibers;

[0188] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0189] Step 5: Wash it with water and ethanol in turn, and dry it;

[0190] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0191] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0192] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0193] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0194] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0195] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0196] Comparative Example 2

[0197] The difference between this embodiment and embodiment 4 is that the spiral fiber is not doped. Specifically:

[0198] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0199] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0200] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0201] Step 3: Place in a 40°C water bath and heat for 1.5 h to form microgels;

[0202] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0203] Step 5: Wash it with water and ethanol in turn, and dry it;

[0204] Step 6: Immerse in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve;

[0205] Step 7: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0206] Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0207] Step 9: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0208] Step 10: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0209] Step 11: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0210] Comparative Example 3

[0211] The difference between this embodiment and embodiment 4 is that the silica-alumina sol is not impregnated. Specifically:

[0212] A method for preparing a micro-nano inorganic particle PP composite material comprises the following steps, measured in parts by weight:

[0213] Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve;

[0214] Step 2: Add 3 parts of sodium trimetaphosphate and 1 part of sodium hydroxide, and stir well to mix;

[0215] Step 3: Add 5 portions of helical fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, continue to stir evenly, and heat in a 40°C water bath for 1.5 h to form a microgel doped with helical fibers;

[0216] Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve;

[0217] Step 5: Wash it with water and ethanol in turn, and dry it;

[0218] Step 6: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0219] Step 7: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles;

[0220] Step 8: Mix 100 parts of PP pellets, 9 parts of micro-nano inorganic particles and 2 parts of sodium dodecyl sulfate;

[0221] Step 9: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0222] Step 10: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0223] Comparative Example 4

[0224] The difference between this embodiment and embodiment 4 is that only modified spiral fibers are added, specifically:

[0225] A method for preparing a modified spiral fiber PP composite material, in parts by weight, comprises the following steps:

[0226] Step 1: Take spiral fibers with a diameter of 0.4-3.6 μm and an aspect ratio of 60-130, immerse them in silica-alumina sol, where the silica sol concentration is 3.0% and the aluminum sol concentration is 3.3%, stir for 15 minutes, take them out and dry them, grind them and pass through a 200-mesh sieve;

[0227] Step 2: Place in an argon protected tube furnace, heat from room temperature to 900°C at a heating rate of 1°C / min, and keep at this temperature for 3.5h;

[0228] Step 3: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain modified spiral fibers;

[0229] Step 4: Mix 100 parts of PP pellets, 9 parts of modified spiral fibers and 2 parts of sodium dodecyl sulfate;

[0230] Step 5: adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 35 rpm, and pellets are obtained. The temperatures of the feeding section, melt plasticizing section and metering section of the extruder are set to 160° C., 190° C. and 190° C., respectively;

[0231] Step 6: After the pellets are dried, they are injection molded using an injection molding machine. The injection molding conditions are: melt temperature of 200°C, screw speed of 35rpm, mold temperature of 90°C, and injection pressure of 80MPa.

[0232] The specifications of the flexural strength, flexural elastic modulus, unnotched impact strength and notched impact strength specimens are 80mm×10mm×4mm; the specifications of the tensile strength and tensile elastic modulus specimens are 170mm×10mm×4mm.

[0233] Tensile strength was tested according to ISO 527-2-2012, test temperature was 23°C, test speed was 5mm / min;

[0234] The tensile elastic modulus is tested according to ISO 527-2-2012, the test temperature is 23°C, and the test speed is 1mm / min;

[0235] The flexural strength and flexural modulus are tested according to ISO 178-2019, with a test speed of 2mm / min and a span of 64mm; the unnotched impact strength and notched impact strength are tested according to ISO179-1-2010, with A-type notch.

[0236] Table 1 Mechanical properties of different embodiments

[0237]

Claims

1. A micro-nano inorganic particle PP composite material, characterized in that: The composition comprises the following components in parts by weight: 100 parts of PP, 8-10 parts of micro-nano inorganic particles and 2 parts of dispersant; The particle size of the micro-nano inorganic particles is ≤75 μm; The preparation method of the micro-nano inorganic particles is as follows, in parts by weight: Step 1: Dissolve 10 parts of carboxymethyl starch in 50 parts of water and stir to fully dissolve; Step 2: Add 2-3 parts of sodium trimetaphosphate and 0.8-1 parts of sodium hydroxide, and stir well to mix; Step 3: Add 3-6 parts of spiral fibers, the diameter of the spiral fibers is 0.4-3.6 μm, and the aspect ratio is 60-130, continue to stir evenly, and heat in a 40°C water bath for 1-1.5 hours to form a microgel doped with spiral fibers; Step 4: Place in a 4°C refrigerator overnight, take out and crush, and pass through a 200-mesh sieve; Step 5: Wash it with water and ethanol in turn, and dry it; Step 6: Immerse in silica-alumina sol, stir for 10-20 minutes, take out and dry, continue to grind and crush through a 200-mesh sieve; the silica sol concentration in the silica-alumina sol is 2.5-3.5%, and the aluminum sol concentration is 3.0-3.5%; the silica-alumina sol is prepared by a Sol-Gel method by preparing Na2SiO3 and Al2(SO4)3 aqueous solutions; Step 7: Place in an argon protected tube furnace, raise the temperature from room temperature to 850-950°C at a heating rate of 1°C / min, and keep at this temperature for 3-4h; Step 8: After cooling to room temperature, take out, wash with water, dry, and pass through a 200-mesh sieve to obtain micro-nano inorganic particles; The method for preparing the spiral fiber in step 3 is: (1) taking discarded coconut shell fiber, loosening it, adding water to steam it, washing it, and drying it to obtain clean coconut shell fiber; (2) adding a NaOH solution with a concentration of 15-20 g / L and a solid-liquid weight ratio of 1:(10-20), pre-soaking at 60-90° C. for 20-60 min, stirring and synchronously ultrasonically oscillating for 2-3 h, and then cyclically extruding and dehydrating and washing with water for 1-3 times to obtain a coconut shell fiber floc; (3) The coconut shell fiber web is subjected to extrusion, dehydration and multi-stage drawing treatment to form spiral fibers, which are then dried.

2. The micro-nano inorganic particle PP composite material according to claim 1, characterized in that: The dispersant includes polyethylene wax, sodium lauryl sulfate, oxidized polyethylene wax and vinyl bisstearamide.

3. The method for preparing a micro-nano inorganic particle PP composite material according to any one of claims 1-2, characterized in that: The following steps are involved: Mix PP granules, micro-nano inorganic particles and dispersant; The mixture was added into a twin-screw extruder for melt blending, extrusion and granulation to obtain pellets, and the temperatures of the feeding section, melt plasticizing section and metering section of the extruder were set to 160° C., 190° C. and 190° C. respectively; After the pellets are dried, they are injection molded by an injection molding machine.

4. The method for preparing a micro-nano inorganic particle PP composite material according to claim 3, characterized in that: The screw length-to-diameter ratio of the twin-screw extruder is 40:1, and the screw speed is 35 rpm.

5. The method for preparing a micro-nano inorganic particle PP composite material according to claim 3, characterized in that: The injection molding conditions are: melt temperature of 200° C., screw speed of 35 rpm, mold temperature of 90° C., and injection pressure of 80 MPa.

Citation Information

Patent Citations

  • Micron-nano silicon carbide / polypropylene composite and preparation method thereof

    CN101735509A